Speaking Difficulties Faced By Islamic Educational Management Students In English For Daily Conversation Class - Efrini, Multi; Yelliza, Merri; Husnani, Husnani (Jurnal Pendidikan Tambusai, 2024)
English for daily conversation is one of the general subjects thought at UIN Mahmud Yunus Batusangar for all majors except English education major. The purpose of this subject is to improve students’ English skills, especially in speaking—daily life speaking. Speaking is a difficult skill because, through speaking, the speaker produces a language, not only by exchanging information and ideas but also emotion. Many problems faced by students in speaking English, and factors caused difficulties in speaking. This study was conducted to find out the speaking difficulties faced by non-English students in English for the Daily Conversation subject. It was classified as a descriptive-qualitative approach. The data of this research was the interview result of the students’ speaking difficulties. The sources of data for this research are the third-semester students of The Islamic Educational Management in 2023- 2024 academic year with the lowest ten final marks. There were some difficulties faced by non-English students in speaking at English for Daily Conversation class; they are linguistics and non-linguistics problems. In terms of linguistic difficulties, students have a lack of vocabulary, poor pronunciation, a lack of grammar mastery, and poor speaking fluency. In terms of non-linguistic difficulties, the students have lack of confidence, anxiety, shyness, lack of motivation, and fear to make a mistake. There were many factors that caused their difficulties in speaking. In conclusion, the non-English students in the Islamic Educational Management class faced some difficulties in speaking that were caused by many factors.